Combining the grazing tolerance trait with forage production in non-dormant alfalfa - Bouton J.H.; Gates R.N.; Hill G.M. (Quality in lucerne and medics for animal production, 2001)
Cultivars developed with selection after overgrazing showed the highest survival in plots exposed to continuous overgrazing and the highest survival in rotationally grazed and hay harvest treatment areas. Grazing tolerant cultivars were higher yielding in the second year. We also evaluated grazing tolerant lucerne as supplemental grazing for a perennial, warm-season grass-based beef cow-calf production system. Grazing tolerant, non-dormant cultivars showed better stand survival and less weed encroachment. An increase in milk production was found for cows with access to lucerne, but no improvement in calf weight gain resulted from lucerne supplemental grazing. Post-weaning performance of calves with access to lucerne was comparable to contemporaries fed hay and grain post-weaning. For calves with access to lucerne post-weaning, performance of animals with prior experience with grazing alfalfa was greater.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)